EFL Vocabulary Mastery of Senior High School Students of SMA N 7 Malang and Its Relationship to Their Ability in EFL Reading Comprehension - RISWANDI, DIKI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Reading Comprehension, Vocabulary, Reading Assessment, Vocabulary Assessment, MIA, Peminatan Bahasa Inggris The present study investigated the correlation between students’ achievement in EFL vocabulary and EFL reading comprehension. The study was done in SMA N 7 Malang. The sample of the research was 30 students which were taken by systematic sampling. This study was quantitative research with correlational method. In collecting data, the writer used a test which consists of 20 items of vocabulary test and 20 items of reading comprehension test as the instrument. The students were asked to do the test of both vocabulary and reading comprehension at the same time. Therefore, the data were in the form of students’ scores from the test. As the study was correlational method and the data gained is ratio data, thus they were computed statistically by using Pearson Product Moment. The result of coefficient correlation (ro) was 0.79 and tvalue (to) was 6.82. Then by df 28, it was compared with rtable and tat 5% significance which is 0.374 and 2.048. It shows that ro is higher than rtable (0.79 > 0.374) and to is higher than ttable (6.82 > 2.048). Since ro was higher than rtable and ‘to’ was also higher than ttable table; therefore the correlation was positive and strong. These mean the alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. Therefore, there was statistically significant correlation between students’ mastery in EFL vocabulary and their EFL reading comprehension.